The Dynamics of International Capital Flows and Internal and External Balance - Tsiang, S. C. (Quarterly Journal of Economics, 1975)
I. Introduction, 195. — II. Formulation of an appropriate function of international capital flow, 197. — III. Reappraisal of Mundell's assignment problem, 200. — IV. Further look into the basic stability of the system, 207.